(1)a 2=2S 1+1=3=3a 1,
当n≥2时,a n+1-a n=(2S n+1)-(2S n-1+1)=2a n,(3分)
∴a n+1=3a n,即
a n+1
a n =3 ,
∴数列{a n}是首项a 1=1,公比为3的等比数列,(4分)
从而得: a n = 3 n-1 ;(6分)
(2)设数列{b n}的公差为d(d>0),
∵T 3=15,∴b 2=5,
依题意a 1+b 1,a 2+b 2,a 3+b 3成等比数列,
则有 ( a 2 + b 2 ) 2 =( a 1 + b 1 )( a 3 + b 3 ) ,
又a 2=3,b 1=b 2+d=5-d,b 3=b 2+d=5+d,
∴64=(5-d+1)(5+d+9),
解得:d=2或d=-10(舍去),(8分)
∵b 1=5-d=5-2=3,
∴ T n =3n+
n(n-1)
2 ×2= n 2 +2n ,(10分)
∵
1
T n =
1
2 (
1
n -
1
n+2 ),
则
1
T 1 +
1
T 2 +…+
1
T n
=
1
2 [(
1
1 +
1
2 +…+
1
n )-(
1
3 +
1
4 +…+
1
n+2 )]
=
1
2 [(
1
1 +
1
2 )-(
1
n+1 +
1
n+2 )]=
3
4 -
2n+3
2(n+1)(n+2) .(13分)